(untitled) (Research, Society and Development, 2021)
This research aims to analyze the process of construction of reading and writing and the psychopedagogical intervention in literacy. In the development of research and to understand how the process of construction of reading and writing takes place, the Theory of Psychogenesis of Writing, developed by Ferreiro and Teberosky (1985), was used for the analysis of the process of acquisition and learning in beginning of literacy. For the foundation of the work, bibliographic research was used with analysis of books, theses, dissertations and articles dealing with the theme. As a result of the research, we conclude that, in order to remedy the learning difficulties, it is understood that it is necessary for the psychopedagogue to know the literacy methods with the objective of contributing to the process of acquiring the reading and writing of the apprentices, privileging the specificities of each individual.